2019
DOI: 10.1111/acel.13015
|View full text |Cite
|
Sign up to set email alerts
|

Aging induces cardiac mesenchymal stromal cell senescence and promotes endothelial cell fate of the CD90 + subset

Abstract: Aging is a major risk factor in the development of chronic diseases, especially cardiovascular diseases. Age‐related organ dysfunction is strongly associated with the accumulation of senescent cells. Cardiac mesenchymal stromal cells (cMSCs), deemed part of the microenvironment, modulate cardiac homeostasis through their vascular differentiation potential and paracrine activity. Transcriptomic analysis of cMSCs identified age‐dependent biological pathways regulating immune responses and angiogenesis. Aged cMSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 36 publications
(42 reference statements)
1
44
0
3
Order By: Relevance
“…The main function of the SASP is to reinforce cell senescence by secreting pro-senescent cytokines such as IL1, IL6, and IL8 [ 130 , 131 , 132 ]. Furthermore, the SASP induces paracrine senescence in neighboring cells [ 133 ].…”
Section: Sasp and Stem Cell Senescence And Agingmentioning
confidence: 99%
“…The main function of the SASP is to reinforce cell senescence by secreting pro-senescent cytokines such as IL1, IL6, and IL8 [ 130 , 131 , 132 ]. Furthermore, the SASP induces paracrine senescence in neighboring cells [ 133 ].…”
Section: Sasp and Stem Cell Senescence And Agingmentioning
confidence: 99%
“…The results showed that mIgG bound KRT10 to form complexes (Figure 3 E). Furthermore, we also found the CD31 + endothelial cells in the heart 23 expressed KRT10 ( Figure S3 ). The results indicate that mIgG can specifically bind KRT10 in vascular endothelial cells in the heart.…”
Section: Resultsmentioning
confidence: 60%
“…In the adult heart, C-MSCs participate in stromal cardiac tissue renewal by differentiating into SMCs and ECs and releasing a variety of paracrine factors responsible for trophic, angiogenic, and anti-inflammatory effects (Martini et al, 2019). Here we report that transplantation of C-MSCs after N1ICD overexpression has a superior and significant effect on cardiac function improvement and attenuation of cardiac fibrosis compared with C-MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that Notch1 activation boosts the function of C-MSCs in the regenerative process. However, Notch1 is altered in aging (Rizzo et al, 2018), which also compromises the function of C-MSCs (Martini et al, 2019). How Notch signaling is affected in the aging heart has not been extensively investigated yet.…”
Section: Discussionmentioning
confidence: 99%